The Effect Of Service Quality And Location On Consumer Satisfaction At Intan Motor Workshop In Cibeber, Bogor Regency - Maulana, Sheikh; Jasmani, Jasmani (Management Science Doctoral Program, Pasundan University, 2024)
This study aims to determine the effect of service quality and location on customer satisfaction at the Intan Motor Workshop in Cibeber, Bogor Regency. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study show that service quality has a significant effect on consumer satisfaction of 62.6%, the hypothesis test obtained t count> t table or (12.796> 1.984). Location has a significant effect on consumer satisfaction of 68.3%, the hypothesis test obtained t count> t table or (8.595> 1.984). Service quality and location simultaneously have a significant effect on consumer satisfaction with the regression equation Y = 6.146 + 0.365X1 + 0.495X2 and the contribution of influence is 73.3%, the hypothesis test obtained F count> F table or (18.770> 3.090).